The allure of controversial brands: preferences for larger logo sizes - Pera, Carolina Saraiva Miranda (2022)
In the subsequent research, I investigate factors that might play a role in people’s reactions to controversy. I propose that brands that take a stand on a controversial matter are perceived to take risks that could potentially damage its reputation. Which, in turn, leads controversial brands to signal power and status as long as observers perceive it as costly and observable (Spencer, 1973). Moreover, because one’s perception of status is filtered and guided through one’s convictions (Levy, Chiu and Hong, 2006)I hypothesize that beliefs concerning one’s personality would play a role to display a large logo from a controversial brand. Provided that there are two types of implicit personalities: entity theorists -believe society uses brands to signal who they represent to others, and incremental theorists -draw situational inferences on why individuals use a brand(Park and John, 2017; Preißinger and Schoen, 2018).I predict that entity theorists, under lack of power would use a controversial brand large logo as a signal to others.